Complex gravity zones and the extension of labour catchment areas in North Transdanubia - Hardi, Tamás (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2014)
The goals of this study are the identification of the centres of gravity of the Northern- Transdanubian cities, including Győr, by using a gravitation model and, based on empirical examination, the definition of manpower catchment areas. Then, we are going to analyze the impact fields determined by two methods and seek explanations for the overlaps and differences of the two delineations, which are also going to be analyzed with the consideration of geographic, social and economic factors. Both examinations were carried out at two dates, covering a timeframe of 10 years.
Keywords: delovna sila; demografija; demography; gravitacijska območja; human migration; Hungary; Madžarska; migracije; Transdanubija